Alternative activators in alkali activated cements - Payá Bernabeu, Jordi; Monzó, José; Borrachero, María Victoria; Soriano, Lourdes; Tashima, Mauro M. (Revista ALCONPAT, 2022)
Alkali activated cements (AAC) require an alkaline component for activating of the precursor. The manufacture of the alkaline activator (AA) involves a very important energy and raw material consumption, so that the carbon footprint (CF) of AAC is basically influenced by this factor. An alternative is the use of other materials for AA preparation. In this work an exhaustive analysis of the different alternatives is carried out: silica-based materials to prepare of alternative silicates and alkaline-based materials. CF is compared relative to commercial Portland cements, and the effect of replacing commercial reagents with alternative activators is analyzed.